Flood relief and rehabilitation in Ormoc experiences and insights of field workers and beneficiaries - Conaco, Maria Cecilia Gastardo; Hernandez, Louie Benedict; Racillo, Jeannette (1993)
Natural cataclysms are almost commonplace in the Philippines. Thus, there is a need for efficient and effective disaster management, both before and after the event. Using the Ormoc case, the researchers attempted to document post-disaster management efforts, specifically the helping process, and to probe into the dynamics of the total help system that mediate the relief and rehabilitation efforts. Highlighted in the study were the need for coordination of relief efforts. The necessity for well-established linkages and networks among the various agencies for more efficient relief efforts were underscored and the major role of government in providing leadership during times of crisis was noted. Above all, the importance of a good pre-disaster management and preparedness program cannot be underemphasized.
Keywords: Emergency management -- Ormoc City (Leyte); Ormoc Disaster, 1992